2009
DOI: 10.3831/kpi.2009.12.4.119
|View full text |Cite
|
Sign up to set email alerts
|

Acupotomy and venesection in Upper Limb Lymphedema and Peripheral neuropathy following Breast Cancer Surgery

Abstract: Purpose: In order to estimate clinical effects of acupotomy and venesection in a patient with peripheral neuropathy and upper limb lymphedema following breast cancer surgery.Methods: From female patient with peripheral neuropathy and upper limb lymphedema following breast cancer surgery was treated with general oriental medicine therapy(acupuncture, moxibustion, cupping, physical therapy, herbal medication) and acupotomy with venesection. Results:The patient's chief complaints-Lt hand numbness, Lt arm edema, L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…[ 12 20 ] Among these, 3 were case series, [ 13 , 14 , 19 ] 5 were single-case reports, [ 12 , 15 – 18 ] and only 1 was a RCT. [ 20 ] Three studies investigated lymphedema, [ 12 , 14 – 15 ] 2 investigated chemotherapy-induced peripheral neuropathy (CIPN), [ 18 , 19 ] 1 investigated hot flushes, [ 13 ] 1 assessed constipation, [ 20 ] and 2 investigated miscellaneous symptoms (nausea, CIPN, dryness of mouth, etc., Table 1 ). [ 16 , 17 ] The excluded studies are listed in Supplementary 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 12 20 ] Among these, 3 were case series, [ 13 , 14 , 19 ] 5 were single-case reports, [ 12 , 15 – 18 ] and only 1 was a RCT. [ 20 ] Three studies investigated lymphedema, [ 12 , 14 – 15 ] 2 investigated chemotherapy-induced peripheral neuropathy (CIPN), [ 18 , 19 ] 1 investigated hot flushes, [ 13 ] 1 assessed constipation, [ 20 ] and 2 investigated miscellaneous symptoms (nausea, CIPN, dryness of mouth, etc., Table 1 ). [ 16 , 17 ] The excluded studies are listed in Supplementary 1.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies involved manual acupuncture to treat the respective symptoms, [ 12 – 17 ] and only 1 study used electro-acupuncture. [ 15 ] One study adopted electric acupoint stimulation, [ 18 ] and another study used auricular acupressure by the patients’ own hands.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acupotomy, widely used in Korea and China, a special form of acupuncture with characteristics of surgical procedures, is widely used for musculoskeletal conditions and is considered an excellent treatment for pain relief [19]. The analgesic effect of acupotomy has been recognized by many clinicians [20]. Moreover, in the previous preliminary experiments, we found that acupotomy has a good clinical effect and safety in the treatment of pain after thoracoscopic surgery.…”
Section: Introductionmentioning
confidence: 77%
“…12,13 Consequently, acupotomy treatment has been applied for various musculoskeletal diseases [14][15][16][17][18][19] and some metabolic diseases such as lymphatic edema. 20 Although the effectiveness of acupotomy on LDH was suggested by several case reports and a pilot study, 13,[21][22][23] a more extensive confirmatory study was needed to confirm the effectiveness and safety of acupotomy on LDH.…”
Section: Introductionmentioning
confidence: 99%